Facile preparation of hierarchical heterostructured TiO2/Bi/Bi2MoO6 photocatalyst for phocatalytic degradation of toluene gas. Issue 6 (13th March 2021) - Sun, Zhiguo; Fan, Jiaming; Feng, Run; Wang, Menglu; Zhou, Yue; Zhang, Li
Abstract: BACKGROUND: In recent years, the emission of volatile organic compounds (VOCs) from different sources has caused huge environmental problems. As a 'green' terminal treatment technology, photocatalytic technology is a competitive technology that has practical application prospects for the emission reduction of VOCs. The core problem of photocatalysis technology is constructing a photocatalyst with higher activity. RESULTS: In this work, a new hierarchical heterostructured photocatalyst of TiO2 /Bi/Bi2 MoO6 was facilely fabricated by solvothermal method with the TiO2 nanoparticles uniformly distributed on the surface of flower‐like Bi2 MoO6 nanospheres. Compared with the bare flower‐like Bi2 MoO6 nanospheres, the band gap width of TiO2 /Bi/Bi2 MoO6 is wider, which helps to improve the Fermi level‐derived oxidation–reduction capacity of the catalyst. N2 adsorption–desorption experiments show that the composite material has a larger specific surface area, which is beneficial to improve the mass transfer efficiency in the gas–solid heterogeneous reaction. Photocatalytic data display that, under irradiation by Xenon lamp for 2 h, the degradation rate of toluene gas over TiO2 /Bi/Bi2 MoO6 reached 26.08%, which is 17.92% higher than that of the bare Bi2 MoO6 nanospheres. CONCLUSION: These results indicate that coupling TiO2 could significantly enhance the photocatalytic degradation effect of toluene over the hierarchical heterostructured TiO2 /Bi/Bi2 MoO6, and this has practical application prospects for the use of photocatalytic technology to treat VOCs pollution. © 2021 Society of Chemical Industry